A Laboratory Investigation of Anxious Cognition: How Subliminal Cues Alter Perceptual Sensitivity to Threat. Issue 4 (October 2013) - Jusyte, Aiste; Schönenberg, Michael
Emotional stimuli represent a category of signals that are relevant for survival. This relevance is reflected in the prioritization of threatening over neutral information, which has been demonstrated for inherently threatening stimuli and stimuli with acquired affective significance. The present study aimed to investigate whether threatening cues presented without conscious awareness have an impact on perceptual judgements. For this purpose, neutral or angry facial expressions associated with prior congruent (Experiment 1), incongruent (Experiment 3) or no aversive learning (Experiment 2) were presented subliminally in a perceptual decision task. During the task, subjects rated mask faces that varied in emotion intensity ranging from neutral to angry. Subjects tended to make more "angry" responses only when the subliminal stimulus was angry and had been previously paired with an aversive experience. These findings may have direct clinical relevance because similar mechanisms could account for cognitive biases in anxiety disorders.